Entre portrait symbolique et vision sociale de la femme. La sirène dans des poèmes choisis de la fin du XIXe siècle - Sasin, Eliza (2023)
This article aims to show the relationship between the woman in the social context of nineteenth-century France and the female portrait presented in symbolist poetry. Allegiances between the philosophical influence of Schopenhauer and Baudelaire, the woman of the theatre as well as the femme fatale and the mermaid, her mythological prototype, are proven. The presented portrait is based on woman’s primal relationship with nature and with artificiality depending on the development in society; the main elements are the dependence of the woman on the man and their mutual manipulation.
Keywords: poetry of Symbolism; water symbolism; femme fatale; French poetry; woman; society of 19th century